In-vessel composting model with multiple substrate and microorganism types - Woodford, Philip Bernard (Kansas State University, 2009)
This research provides a deterministic model of in-vessel composting, based on Monod’s growth kinetics, to mirror biological-mixture decomposition. Existing models predict temperature curves assuming a single temperature-range organism, using a soluble (simple sugar) substrate, with bacteria as the microorganism, and they ignore the different temperature range environments that impact the growth rates of mesophilic and thermophilic microorganisms. The new computer-simulated model, written in MATLAB® by The MathWorks, has six unique features. First, three major carbon chain substrate groups are utilized: soluble, hemicellulose/cellulose, and lignin. An additional substrate group is used for inert substrates. Second, three major microorganism groups are utilized: bacteria for soluble substrate, actinomycetes for cellulose substrate, and fungi for lignin substrate. Third, two temperature-range microorganisms are included: mesophilic and thermophilic. Fourth, the model accounts for the death of microorganisms as the temperature transitions between the temperature ranges. Most of the dead cellular mass is returned to soluble substrate for reutilization and a portion is considered resistant to biological decomposition and is added into the lignin substrate. Fifth, stoichiometric equations account for substrate and microorganism compositions, oxygen and nitrogen requirements, and carbon dioxide and water production. Sixth, the relationship between biological activity and water is better defined. Experimental research was conducted to validate the model. Laboratory analysis distinguished the substrate types. The results indicate the model did differentiate between different levels of substrate types, and the mesophilic and thermophilic microorganism types. Also, the model did differentiate between the bacteria, actinomycetes and fungi. The influence was small, however, because of the different maximum growth rates of the three types of microorganisms. Returning dead microbes to the substrate pools as a result of temperature transitions affected the model results positively. Additional research is needed to account for the influence of volume reduction, develop a better microbial growth curve, include particle size influence, add temporal temperature fluctuations to the external boundary conditions, incorporate pH and nitrogen availability, and develop a three-dimensional model. KEY WORDS. Aerobic composting, mathematical composting model, substrate types, microorganism types, microorganism temperature range, mesophilic, thermophilic, microbial death utilization, moisture composting relationship.
Keywords: Composting; Mathematical composting model; Substrate types; Mesophilic; Thermophilic; Microbial death utilization; Engineering, Agricultural (0539)